A new deep-sea eelpout of the genus Pyrolycus (Teleostei: Zoarcidae) associated with a hydrothermal seep on the Pacific margin of Costa Rica - Frable, Benjamin W.; Seid, Charlotte A.; Bronson, Allison W.; Møller, Peter Rask (Zootaxa, 2023)
A new species of the zoarcid genus Pyrolycus Machida & Hashimoto, 2002, Pyrolycus jaco sp. nov., is described from a hydrothermal seep environment named Jacó Scar in the eastern Pacific of Costa Rica. Four specimens were collected in 2018 between 1746–1795 m among tubeworm colonies around the seep. The new species is differentiated from its two western Pacific congeners by having a shorter head, snout, jaw, and pectoral fins. It is further diagnosed by having three postorbital pores and two occipital pores. Molecular sequences of the cytochrome c oxidase I gene are provided and are the first for the genus. The character states indicating miniaturization in this species are discussed. This is the first vertebrate species known from this composite reducing ecosystem and is the fourth hydrothermally-associated zoarcid from the eastern Pacific.